Note on the seasonal use of lowland and highland habitats by the West African Chimpanzee Pan troglodytes verus (Schwarz, 1934) (Primates: Hominidae): Implications for its conservation - P.I. Ndiaye; G. Galat; A. Galat-Luong; G. Nizinski (Journal of Threatened Taxa, 2013)
The West African Chimpanzee Pan troglodytes verus is endangered. In order to gain insight into the survival potential of this subspecies in Senegal (West Africa), we investigated relationships between this primate and its habitat, particularly from a novel perspective: the influence of the topography on the seasonality of its distribution within its habitat. In Senegal chimpanzees are rarely seen in the wild, particularly outside of protected areas, which is where the present study was conducted on the basis of nest census findings (N=436). According to our observations between March 1998 and March 2000, we established that chimpanzees nested in the gallery forest during the dry season and higher areas (hills and plateaus, plateau edge gallery forests) during the rainy season. Valley flooding during the rainy season may be the major reason for chimpanzees to nest in the highlands. The results can help conservation managers to protect the species.